Organisational Manoeuvres to Manage Human Resource Development Strategically: A Review of Strategic HRD Factors - Sthapit, Arhan (PYC Nepal Journal of Management, 2021)
In managing the rapidly changing environment context, human resources and talents are probably the only organisational resource that managers can resort to, in their pursuit of sustainably steering the organisation through the turbulent course, including the one of the COVID-19 pandemic now. Managers should push forward organisational manoeuvres to manage their human resource development (HRD) function by embodying strategic factors in a commensurate manner. It requires them to strategize the way they train and develop their human resources and talents; that is, the process of strategic HRD. Therefore, this paper reviewed the past literature to identify the strategic HRD factors, which are the organisational manoeuvres essential to manage HRD strategically. Based on the critical deliberations on the previous literature, it infers that there are seven key strategic factors that strategize HRD in an organisation. It helps build an agile, resilient organisation that can sustain in both normal and crisis times.